Social Information Processing in Preschool Children: Relations to Sociodemographic Risk and Problem Behavior - Ziv, Yair (2011)
Using a multi-component, process-oriented approach, the links between Social Information Processing in the preschool years and a) sociodemographic risk, and b) behavior problems in preschool, were examined in a community sample of 196 children. Findings provided support for our initial hypotheses that aspects of social information processing in preschool are related to both sociodemographic risk and to behavior problems in preschool. Response evaluation, and in particular, the positive evaluation of an aggressive response, were related to both sociodemographic risk and children’s aggressive behavior and partially mediated the links between sociodemographic risk and aggressive behavior in preschool.